A Dual-Protocol File Transfer Application: Balancing Speed and Reliability in Peer-to-Peer Networks - Rajasekaran, G; Rajest, S. Suman; Regin , R; Sameer Ali , M. Mohamed; Kumar, S. Ramesh (International Journal on Human-Computing Studies, 2025)
In today’s digital era, secure and efficient file transfer mechanisms are crucial as digital communication becomes increasingly prevalent. This paper presents a File Transfer Application that enables collaborative file sharing among multiple users over a network. The application uses a client-server architecture, integrating UDP for fast communication and TCP for secure and reliable file transfers. The server manages client registrations, maintains a dynamic table of active users, and broadcasts file availability updates, fostering real-time collaboration. Clients register with the server by sending their details and receive a list of online peers. Users can share files or request them directly from others, promoting peer-to-peer interaction. A simple command-line interface allows easy navigation, making the application accessible to users with varying technical backgrounds. File transfers utilize TCP to ensure data integrity, while UDP handles lightweight communication, minimizing latency. The system allows clients to disconnect gracefully, updating the server and other users accordingly. Tested in various environments, including simulations on a single machine, the application demonstrates its robustness in handling concurrent users effectively. This paper not only highlights key networking and socket programming concepts but also lays the groundwork for future enhancements like encryption and authentication, ensuring secure, scalable digital file sharing.